STRATEGI PENGEMBANGAN INDUSTRI PENGOLAHAN HASIL PERTANIAN DAN LINGKUP PEMASARANNYA DI KABUPATEN SAROLANGUN - Mara, Armen (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
This Research was conducted in 2018 using data Disperindagkop Directory Sarolangun District in 2016. Industrial development strategy is determined by the level of development of industry it self, the availability of raw materials locally, and market coverage has been mastered. Field data collection are carried out with a survey and take a sample of 30 industries, namely food industry, raw material of food industry, woven industrial, and industrial wood. The data analysis is done deskriptive, tabulation, and cross tabulation. The results showed, there were as many as 15 kinds of agricultural product processing industry with the potential to be developed as it is supported by a local farm product raw materials sufficient. The potential of the industry shows that the number of industries as many as 516 units and total workforce of 1,540 people. In Sarolangun District, there are around 272 203 inhabitants with an average population density of more than 44 people per km2, and have at least 10 (ten) regional growth centers. The identification results show that each industry has its problems are diverse and generally include production engineering problems and place of business, business management issues, the issue of capital, and marketing issues. Based on the economic value of each industry can be divided into four (4) levels, which is the industry that do not have economic value, economic value of small, medium economic value and high economic value. Results of the analysis showed, there are relationship between the size of the market with the high economic value coverage. Where the higher economic value, the greater the market coverage. Strategy development of agricultural product processing industry can be done by expanding the market through promotion, technical assistance through mentoring, capital, and organizational development of small businesses and cooperatives ***). Key word: agricultural processing industry